Earning Management Sebagai Variabel Intervening Antara Mekanisme Good Coorporate Governance dan Corporate Social Responsibility Terhadap Agresivitas Pajak - Siti Famila Karuniansyah; Saiful Anwar (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
Tax aggressiveness is the way to minimize the tax expense by tax avoidance and tax evasion. The purpose of this study was to analyze the effect of good corporate governance as proxied by institutional ownership and managerial ownership, as well as corporate social responsibility on the tax aggressiveness of mining companies listed on the IDX in 2015-2019 through earnings management as an intervention variable. The method of determining the sample using purposive sampling technique, in order to obtain a sample of 7 companies with 35 observational data. The type of data used is secondary data from annual mining company reports. Data were analyzed using SEM PLS with PLS 6.0 software program. The results prove that institutional ownership has a negative effect on tax aggressiveness, while managerial ownership, CSR, and earnings management have no effect on tax aggressiveness. CSR has a positive effect on management earnings, while institutional ownership and managerial ownership do not have effect on earnings management. Institutional ownership, managerial ownership, and CSR do not have effect on tax aggressiveness through earnings management